2020
DOI: 10.18620/ctt-1866-8836-2020-9-2-47-59
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis is a potential marker of effective microbiota transplantation in acute graft-versus-host disease treatment

Abstract: Summary Fecal microbiota transplantation (FMT), as any other medical procedure, requires standardization of results, approaches, monitoring of its dynamics and microbiota engraftment evaluation. The aim of the present study was to compare efficiency and results of PCR and 16S RNA-based sequencing in order to trace the dynamics of microbiota composition after FMT. Patients and methods The prospective, single-center study included 27 patients with acute intestinal and chronic (overlap syndrome) graft-versus-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Goloshchapov and colleagues reported the successful treatment of steroid refractory acute or chronic GVHD with a complete response in five (38%) and partial response in 13 (100%) of the 13 treated patients 120 days after two to three days of FMT treatment. 65 In a case study, Mao and colleagues 67 reported the successful treatment of a 31-year-old male with steroid-refractory intestinal GVHD after two cycles of treatment with FMT.…”
Section: Indications and Patient Characteristics In Studies Of Encapsulated Fmt Treatment For Conditions Other Than CDImentioning
confidence: 99%
See 2 more Smart Citations
“…Goloshchapov and colleagues reported the successful treatment of steroid refractory acute or chronic GVHD with a complete response in five (38%) and partial response in 13 (100%) of the 13 treated patients 120 days after two to three days of FMT treatment. 65 In a case study, Mao and colleagues 67 reported the successful treatment of a 31-year-old male with steroid-refractory intestinal GVHD after two cycles of treatment with FMT.…”
Section: Indications and Patient Characteristics In Studies Of Encapsulated Fmt Treatment For Conditions Other Than CDImentioning
confidence: 99%
“…In four studies, the safety and effects of encapsulated FMT on graft-versus-host disease in patients post allogeneic haemopoietic cell transplantation were examined in a total of 28 patients. [64][65][66][67] In a case study, Kaito and colleagues tested FMT as a third-line treatment in a patient with acute gut graft-versus-host disease (gGVHD) and concluded that improvement of diarrhoea from stage 3 (>1500 ml/day) to stage 1 (<500 ml/day) after two cycles of FMT was possibly caused by the treatment. 66 In an open-label pilot study by DeFilipp and colleagues 64 primarily investigating safety, FMT was considered safe and increased faecal diversity in the 13 treated patients.…”
Section: Indications and Patient Characteristics In Studies Of Encaps...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteroides fragilis belongs to the Bacteroides species. The B. fragilis strains that lack the enterotoxin gene, display many major benefits (Round and Mazmanian, 2010;Goloshchapov et al, 2020). The capsular polysaccharide B. fragilis (PSA), which can modulate microbiota-host interactions, plays the most important function in this.…”
Section: Bacteroides Fragilismentioning
confidence: 99%
“…NGS applications in medical research are versatile. Via their intended use, high-throughput sequencing techniques can be split into the following groups: (1) analysis of entire genome (whole-genome sequencing, WGS); (2) analysis of protein-coding genes in a genome (whole-exome sequencing, WES); (3) analysis of particular disease-causing gene sequences (from clinical exomes embracing some 4000–5000 clinically relevant genes, to kits for small target regions of one–three genes or loci); (4) transcriptome sequencing (RNA-seq); and (5) analysis of bacterial microbiome biological diversity, Table 1 [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%